Coordinated development of energy-saving and emission-reduction evolution systems in the Yangtze River delta. (2016) - Fu, Min; Hua, Aiqin; Fan, Xinghua; Fang, Guochang; Tian, Lixin
Development trends differ in different regions although China has gained steady development in the society, economy, energy and the environment according to its national strategy. The Energy-Saving and Emission-Reduction (ESER) evolution system can synthetically reflect the development trend of energy, environment and economy of a region. Based on the good efficiency of impulsive control, coordinated development of ESER evolution systems is researched by using synchronisation theory as the regulation theory for regional coordinated development. First, the synchronisation is realised with the impulsive control theoretically. Parameters of the evolution system are estimated from real data about energy and economy. Furthermore, the realisation of impulsive control is verified with fixed parameters and showed by numerical simulations. The evolution trend of energy intensity is obtained from the ESER system, which fits the actual developing trend well.